Two Worlds, One Identity: Postcolonial Reading of Space in Sherman Alexie's The Absolutely True Diary of a Part-Time Indian - Angelique Sheva Kurniawan; Zuhrul Anam (Universitas Islam Negeri Palopo, 2026)
This study examines how the reservation shape’s identity in Sherman Alexie’s The Absolutely True Diary of a Part-Time Indian (2007). Rather than treating the setting as a passive background, this paper contributes to postcolonial spatial studies by showing how the reservation actively constructs identity before any physical movement takes place. This qualitative study applies Sara Upstone’s concepts of